2022
DOI: 10.1039/d2fo02594a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between different forms of dietary choline and ovarian cancer survival: findings from the ovarian cancer follow-up study, a prospective cohort study

Abstract: Higher levels of pre-diagnosis fat-soluble choline intake was associated with better overall survival of ovarian cancer, and this association was more attributed to phosphatidylcholine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…24,27 The previous studies confirmed the validity and reliability of the food frequency questionnaire. 26,29 The Spearman correlation coefficients and intraclass correlation coefficients for reproducibility were above 0.5 for most food groups, and the correlation coefficients between the FFQ and weighed dietary records also satisfied this condition (range: 0.3–0.7). All patients reported the frequencies of each food item consumed in the year before they were diagnosed with OC.…”
Section: Methodsmentioning
confidence: 66%
“…24,27 The previous studies confirmed the validity and reliability of the food frequency questionnaire. 26,29 The Spearman correlation coefficients and intraclass correlation coefficients for reproducibility were above 0.5 for most food groups, and the correlation coefficients between the FFQ and weighed dietary records also satisfied this condition (range: 0.3–0.7). All patients reported the frequencies of each food item consumed in the year before they were diagnosed with OC.…”
Section: Methodsmentioning
confidence: 66%